2019
DOI: 10.1128/iai.00077-19
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Sialic Acid by Nontypeable Haemophilus influenzae Increases Complement Resistance through Decreasing IgM-Dependent Complement Activation

Abstract: Although nontypeable Haemophilus influenzae (NTHi) is a humanspecific nasopharyngeal commensal bacterium, it also causes upper respiratory tract infections in children and lower respiratory tract infections in the elderly, resulting in frequent antibiotic use. The transition from symbiotic colonizing bacterium to opportunistic pathogen is not completely understood. Incorporation of sialic acids into lipooligosaccharides is thought to play an important role in bacterial virulence. It has been known for more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Sialic acid significantly reduced the amount of IgM bound to this strain (Fig. 3A), consistent with a previous report demonstrating that sialic acid uptake confers decreased IgM binding to NTHi (23). However, IgG binding was unaffected by the presence of sialic acid (Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Sialic acid significantly reduced the amount of IgM bound to this strain (Fig. 3A), consistent with a previous report demonstrating that sialic acid uptake confers decreased IgM binding to NTHi (23). However, IgG binding was unaffected by the presence of sialic acid (Fig.…”
Section: Resultssupporting
confidence: 92%
“…The majority of naturally occurring antibody directing the complement-mediated killing of NTHi is specific to the LOS, and anti-LOS IgM titers correlate with increased serum bactericidal activity (25). A recent report showed that sialic acid uptake-dependent inhibition of IgM binding correlated with the reduced sensitivity of NTHi to classical pathway-mediated killing in NHS (23). Consistent with these observations, we confirmed that growth on sialic acid conferred to NTHi protection from killing by the classical pathway of complement (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike Neu5Ac, Kdn does not protect against serum and whole blood killing. Incorporation of Neu5Ac on LOS allows NTHi to resist complement-mediated serum killing (88)(89)(90)(91). Since Kdn can be incorporated into LOS, we asked whether its presence affected NTHi survival in human sera.…”
Section: Resultsmentioning
confidence: 99%
“…Binding of IgM to the bacterial surface is associated with increased bacterial killing of NTHi. Previously, we used IgA/IgM-deficient serum to determine the contribution of IgM in complement-mediated killing of NTHi strains (4,9,10). In order to determine the contribution of IgM in complement-mediated killing of invasive NTHi strains, we determined binding of IgG and IgM to the bacterial surface and bacterial killing of 48 NTHi strains divided into four equal groups based on the quantiles for survival in 5% NHS (Fig.…”
Section: Resultsmentioning
confidence: 99%